Strategi Dinas Pendidikan Kabupaten Bojonegoro dalam Pelaksanaan Sekolah Inklusi - Dian Nur Afifah; Ana Kumalasari; Musta’ana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Inclusive education is education that provides opportunities for students with special needs to participate in learning with general students. This research describes the strategy of the Bojonegoro Education Office for implementing inclusive schools. This research uses qualitative research with a case study approach. Data collection techniques include observation, interviews, and documentation. The results of the research show that implementation of inclusive education in Bojonegoro has not run maximally because several problems occur, such as there is still resistance from communities towards children with special needs; there are limited competent special guidance teachers; learning curriculum still same as general students; and easily accessible learning media still less than optimal. However, on the other hand, the strategy of the Education Office in implementing inclusive education in Bojonegoro can be said to be quite good, this can be seen from the readiness of the Education Office to provide facilities needed by students with special needs and the existence of BOS funds helps meet the needs of students with special needs. Apart from that, there is also the ULD Trandiksus program which will be launched by the Ministry through BPPMP, in which case the Education Office will also provide supporting facilities for every inclusive education activity.